The influence of pelletRAP™ rejuvenator on the mechanical properties of reclaimed asphalt pavement - Putra Jaya, Ramadhansyah; Al-Saffar, Zaid Hazim; Haryati, Yaacob; M. K. I., Mohd Satar; N. S., Shah Rull; A., Mohamed; N. A., Hassan; M. N. M., Warid (IOP Publishing Ltd, 2021)
In the last decade, the use of reclaimed asphalt pavement (RAP) resulted from asphalt milling process has been widely increased for economic and environmental reasons. However, RAP mixtures have undesired characteristics, such as higher stiffness and low flexibility. In this case, the rejuvenators should be used for restoring the properties of RAP which were lost during service life. In the present research, the mechanical properties of 100% RAP incorporating various percentages of PelletRAP™ rejuvenator were evaluated via stability, flow, stiffness, indirect tensile strength (ITS), moisture damage and Cantabro loss measurements. The results showed that the rejuvenated mixtures containing 4% of PelletRAP™ exhibited better performance in terms of stability, cracking and moisture damage resistance, as well as durability, compared with virgin mixtures. Thus, it can be concluded that 100% RAP can be renovated and re-used in the pavement if it is mixed with an appropriate prescription of PelletRAP™. The proposed of incorporating PelletRAP™ with RAP is beneficial in the improvement of sustainability and cost-efficiency of the asphalt mixtures industry.